2017
DOI: 10.3892/ol.2017.6178
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling in patients with hepatocellular carcinoma of familial aggregation and hepatitis B virus infection

Abstract: Abstract. Numerous studies have suggested that microRNAs (miRNAs) potently affect hepatocarcinogenesis. However, the miRNA expression profiling in patients with hepatocellular carcinoma (HCC) of familial aggregation and hepatitis B virus (HBV) infection has not been elucidated. In the present study, the plasma miRNA expression profiles of 3 patients with HCC with familial aggregation of HCC and HBV infection and 1 healthy volunteer were examined by microarray analysis, in order to identify relevant miRNAs invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Besides miR-138-5p, 4 miRNAs (miR-135a-1, miR-let-7 g, miR-1226, miR-564) out of total 16 miRNAs at this locus have been reported to perform tumor suppressive functions in various cancers 127 131 . Furthermore, upregulation of six miRNAs has been identified in different cancer types, including miR-4271 132 , miR-191 133 135 , miR-425 136 138 , miR-4793 139 , miR-2115 140 , and miR-4443 141 , suggesting potential oncogenic functions in these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Besides miR-138-5p, 4 miRNAs (miR-135a-1, miR-let-7 g, miR-1226, miR-564) out of total 16 miRNAs at this locus have been reported to perform tumor suppressive functions in various cancers 127 131 . Furthermore, upregulation of six miRNAs has been identified in different cancer types, including miR-4271 132 , miR-191 133 135 , miR-425 136 138 , miR-4793 139 , miR-2115 140 , and miR-4443 141 , suggesting potential oncogenic functions in these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, levels of miR-21 in serum exosomes are significantly higher in patients with HCC compared to controls [6, 7]. In whole serum, several studies have identified potential diagnostic miRNAs [814]; however, no consensus has been reached on a panel of miRNAs that robustly identifies HCC at an early stage of the disease. In tissue, several miRNAs are found to be dysregulated between tumor and normal tissue [1519], for instance miR-21, miR-199, and miR-221.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al7 reported in their study that a panel of 3 miRNAs when combined with AFP had a higher diagnostic efficacy in the diagnosis of HCC than AFP alone. The current study revealed a significant difference in miR-215 expression levels among the three studied main groups.…”
Section: Discussionmentioning
confidence: 99%
“…Mature miRNAs may interact with the 3′-untranslated regions (UTRs) of target mRNAs to form RNA-induced silencing complexes, resulting in inhibition of translation or mRNA cleavage 6. As well, previous studies have revealed that miRNAs may regulate gene expression at posttranscriptional level and perform a role in regulating epigenetic machinery, including DNA methylation and histone modification 7…”
Section: Introductionmentioning
confidence: 99%